Lean strategies to overcome low volume and high variety for enhanced delivery performance. (13th February 2020) - Ramachandran, G.M.; Neelakrishnan, S.
Global competition have made customers to pick and choose application specific customised products or services. At situations the market demands low volume and high variety products (LVHVs). Lean manufacturing (LM) methodology is growing in parallel in this era, as it reduces and or eliminates waste and strengthens firm's competitiveness. It is seen that in mass and batch production firms, the results of lean were significant but when applied to LVHV, the results were limited. This paper reviews the various challenges that are involved in LVHV product manufacturing firm and detailed analysis performed in supply chain delivery performance that is on time receipt of material (OTR). This paper considered real time data of industrial valve manufacturing company that produces LVHV products. Analysis is performed on the firm's product level sales volume and variety then component level purchase data analysed for firm's order lead time and supplier delivery time to conclude that restructuring is required in the firm's operations towards improving the order lead time for LVHV components procurement through suitable lean strategies.